Assessing the importance of school administration (administrative staff) in elementary schools - Nuraisah, Nuraisah; Abeng, Andi Tenri; Irawanda , Gita (Privietlab, 2025)
This article aims to examine the importance of school administration through the role of administrative staff (Tata Usaha) in elementary schools, using a qualitative approach based on a literature review of academic studies, scientific books, and the latest educational policies. The findings indicate that administrative staff play a crucial role in ensuring the smooth operation of educational management processes, from student data management, financial documentation, and academic archiving to internal coordination. Despite its strategic function, this role is often overlooked, especially in many public elementary schools in Indonesia that do not yet have official administrative staff positions. The absence of this role has led to the administrative burden being shifted to teachers and principals, thereby diverting their focus from core instructional duties. A well-functioning school administration enhances institutional efficiency, supports data-driven decision-making, and strengthens public accountability in education funding. However, challenges such as the lack of structural recognition for the administrative role at the elementary level, minimal professional training, and inadequate regulatory frameworks remain major obstacles. Therefore, the institutionalization of administrative staff in elementary schools must be promptly realized through affirmative policies, continuous competency development, and a paradigm shift towards a more professional school management system. This study concludes that administrative staff are not merely technical support personnel but strategic actors in building an accountable, orderly, and sustainable basic education system. The presence of administrative staff in elementary schools is not an option but a necessity for the delivery of quality basic education services.